Preclinical evaluation of a chemically detoxified pneumolysin as pneumococcal vaccine antigen - Philippe Hermand; Annick Vandercammen; Emmanuel Mertens; Emmanuel Di Paolo; Vincent Verlant; Philippe Denoël; Fabrice Godfroid (Taylor & Francis Group, 2017)
The use of protein antigens able to protect against the majority of Streptococcus pneumoniae serotypes is envisaged as stand-alone and/or complement to the current capsular polysaccharide-based pneumococcal vaccines. Pneumolysin (Ply) is a key virulence factor that is highly conserved in amino acid sequence across pneumococcal serotypes, and therefore may be considered as a vaccine target. However, native Ply cannot be used in vaccines due to its intrinsic cytolytic activity. In the present work a completely, irreversibly detoxified pneumolysin (dPly) has been generated using an optimized formaldehyde treatment. Detoxi-fication was confirmed by dPly challenge in mice and histological analysis of the injection site in rats. Immunization with dPly elicited Ply-specific functional antibodies that were able to inhibit Ply activity in a hemolysis assay. In addition, immunization with dPly protected mice against lethal intranasal challenge with Ply, and intranasal immunization inhibited nasopharyngeal colonization after intranasal challenge with homologous or heterologous pneumococcal strain. Our findings supported dPly as a valid candidate antigen for further pneumococcal vaccine development.